Systemic microvascular endothelial dysfunction is associated with reduction of left ventricular ejection fraction in chronic Chagas disease patients. (25th November 2020) - Kasal, D; Britto, A; De Lorenzo, A; Verri, V; Tibirica, E
Abstract: Introduction: Chagas disease (CD) affects millions of patients around the world, many of whom may develop cardiovascular complications, including heart failure and stroke. Notwithstanding, little is known about the effects of CD in the reactivity of the systemic microcirculation. Purpose: The present study aims to compare the microvascular reactivity (MR) of a group of patients in the chronic phase of CD with healthy volunteers, matched for sex and age. In addition, we sought to evaluate the association between MR and left ventricular ejection fraction (LVEF) in CD patients. Methods: Systemic microvascular flow and endothelium-dependent vasodilation were assessed using laser speckle contrast imaging, coupled with acetylcholine (Ach) iontophoresis in the forearm skin. Vascular reactivity data were expressed as area under the curve (AUC) of Ach-induced vasodilation. Anthropometry, medications, biochemistry, and echocardiographic data were obtained from medical records. Results: Thirty-six patients were compared to 25 healthy individuals (controls). Ach-induced vasodilation was higher in controls, when compared to patients (maximum increase of microvascular flow from baseline of 106% and of 48% respectively, P<0.0001; Mann Whitney test). There was a significant association between LVEF, stratified into quartiles, and MR (P value for linear trend = 0.002; one way ANOVA, Figure 1). In addition, there was no difference in MR between CD patients with normal LVEF and the control group. In CD patients, MR was independent of the presence of arterial hypertension or diabetes. Conclusion: We have shown that the reduction of MR is associated with a decrease of LVEF in a group of chronic CD patients. The results were not affected by comorbidities, such as hypertension or diabetes. The evaluation of systemic endothelial function may be useful to tailor therapeutic and preventive approaches, targeted at systolic left ventricular failure associated with chronic CD cardiomyopathy. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Fundação de Amparo à Pesquisa do Estado do Rio de Janeiro